METAPHORIC MOTION PICTURES IN SOCIAL NETWORKS - Namitcheishvili, Khatia (Online Journal of Humanities ETAGTSU, 2020)
This paper explores specific features and the role played by pictorial metaphors as employed in social networks in a cross-cultural context (using the examples of Georgian and English languages) and discusses the cases when motion pictures or so-called GIFs work as pictorial metaphors. However, not all of the motion pictures or GIFs are considered to be pictorial metaphors. The paper will focus on the items conveying metaphoric concepts and discuss their peculiarities and features. Specifically, the aims of this paper include the following: To explore the peculiarities of the usage of pictorial metaphors in social networks and reveal a new type of representation of this stylistic device. To show the ways motion pictures and GIFs are employed in social networks, reveal their specific features and the reasons for their popularity. The theoretical background of the research is Charles Forceville’s fourfold distinction of pictorial metaphor into Hybrid metaphor; Contextual metaphor; Pictorial simile and Integrated metaphor The empirical data this paper is based on embrace the relevant examples from social networks, such as Facebook. Full Text (PDF)